Umbilical Cord‐Derived Mesenchymal Stem Cell‐Derived Exosomal MicroRNAs Suppress Myofibroblast Differentiation by Inhibiting the Transforming Growth Factor‐β/SMAD2 Pathway During Wound Healing. (7th July 2016) - Fang, Shuo; Xu, Chen; Zhang, Yuntong; Xue, Chunyu; Yang, Chao; Bi, Hongda; Qian, Xijing; Wu, Minjuan; Ji, Kaihong; Zhao, Yunpeng; Wang, Yue; Liu, Houqi; et al.
Abstract : Excessive scar formation caused by myofibroblast aggregations is of great clinical importance during skin wound healing. Umbilical cord‐derived mesenchymal stem cells (uMSCs) reduced scar formation and myofibroblast accumulation in a skin‐defect mouse model. A novel role of exosomal microRNAs in uMSC‐mediated therapy was demonstrated, suggesting that the clinical application of uMSC‐derived exosomes might represent a strategy to prevent scar formation during wound healing. Abstract : Excessive scar formation caused by myofibroblast aggregations is of great clinical importance during skin wound healing. Studies have shown that mesenchymal stem cells (MSCs) can promote skin regeneration, but whether MSCs contribute to scar formation remains undefined. We found that umbilical cord‐derived MSCs (uMSCs) reduced scar formation and myofibroblast accumulation in a skin‐defect mouse model. We found that these functions were mainly dependent on uMSC‐derived exosomes (uMSC‐Exos) and especially exosomal microRNAs. Through high‐throughput RNA sequencing and functional analysis, we demonstrated that a group of uMSC‐Exos enriched in specific microRNAs (miR‐21, ‐23a, ‐125b, and ‐145) played key roles in suppressing myofibroblast formation by inhibiting the transforming growth factor‐β2/SMAD2 pathway. Finally, using the strategy we established to block miRNAs inside the exosomes, we showed that these specific exosomal miRNAs were essential for the myofibroblast‐suppressing and anti‐scarring functions of uMSCs both in vitro and in vivo. Our study revealed a novel role of exosomal miRNAs in uMSC‐mediated therapy, suggesting that the clinical application of uMSC‐derived exosomes might represent a strategy to prevent scar formation during wound healing. Significance: Exosomes have been identified as a new type of major paracrine factor released by umbilical cord‐derived mesenchymal stem cells (uMSCs). They have been reported to be an important mediator of cell‐to‐cell communication. However, it is still unclear precisely which molecule or group of molecules carried within MSC‐derived exosomes can mediate myofibroblast functions, especially in the process of wound repair. The present study explored the functional roles of uMSC‐exosomal microRNAs in the process of myofibroblast formation, which can cause excessive scarring. This is an unreported function of uMSC exosomes. Also, for the first time, the uMSC‐exosomal microRNAs were examined by high‐throughput sequencing, with a group of specific microRNAs (miR‐21, miR‐23a, miR‐125b, and miR‐145) found to play key roles in suppressing myofibroblast formation by inhibiting excess α‐smooth muscle actin and collagen deposition associated with activity of the transforming growth factor‐β/SMAD2 signaling pathway.